Field Model for Complex Ionic Fluids: Analytical Properties and Numerical Investigation (Communications in Computational Physics, 2021)
In this paper, we consider the field model for complex ionic fluids with anenergy variational structure, and analyze the well-posedness to this model with regularized kernels. Furthermore, we deduce the estimate of the maximal density function to quantify the finite size effect. On the numerical side, we adopt a finite volume scheme to the field model, which satisfies the following properties: positivity-preserving, mass conservation and energy dissipation. Besides, series of numerical experiments are provided to demonstrate the properties of the steady state and the finitesize effect by showing the equilibrium profiles with different values of the parameterin the kernel.
Keywords: Complex ionic fluids; variational structure; finite size effect; finite volume method.